Mengubah Perilaku Maladjusted Akibat Stres dengan Terapi Shalat Dhuha - Moh. Sholeh (Universitas Negeri Malang, 2016)
There is a basic need in counselling which has not fulfilled yet. This is because there is no counselling strategy which is set up based on the Islamic value. To meet this need the writer tried to do the research on the correlation between dhuha prayer and the behaviour change maladjusment caused by stress. This research is experimental with 20 students of SMU Hidayatullah Surabaya. To obtain the data, the writer used the questionnaire. The data analysis used is the product moment technique. The result proved that there is the significant correllation between Dhuha prayer and the behaviour change maladjusment caused by the stress which is pointed with the figures = 0,8837 = 0,70-0,90.